Effect of brewing conditions on the physicochemical and antioxidant properties of coffee cascara infusions from the Benguet Region - Sanchez, Laetitia C.; Sanchez, Rowena Grace R. (Quezon City University of the Philippines Diliman, 2025)
Coffee cascara, a by-product of coffee processing, has emerged as a sustainable ingredient with potential functional and nutritional applications. This study aimed to evaluate the physicochemical and antioxidant properties of cascara infusions from the Benguet region in the Philippines, focusing on the influence of cascara processing (mixed and natural process), proportion (1%, 3%, 5%), and steeping time (5 and 10 minutes). Using total phenolic content (TPC) and DPPH radical scavenging assays, significant differences were observed based on processing type, with mixed-processed cascara (ACOGMAC) outperforming naturally processed cascara (ECC) in antioxidant performance. TPC and antioxidant activity (IC₅₀) improved with increasing concentration, though a plateau was observed between 3% and 5%, likely due to extraction saturation. Processing method and proportion significantly affected pH, TSS, color, TPC and antioxidant activity parameters, while steeping time only affected infusion color values. The findings support cascara’s potential as a functional beverage ingredient, demonstrating high phenolic content and antioxidant activity comparable to or exceeding conventional botanical teas.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Coffee -- Processing -- Philippines; Functional foods -- Philippines; Coffee cascara; Antioxidant activity; DPPH radical scavenging assay